Recovering Moho parameters using gravimetric and seismic data - Abrehdary, Majid (KTH, Geodesi och satellitpositionering, 2016)
Isostasy is a key concept in geoscience to interpret the state of mass balance between the Earth’s crust and mantle. There are four well-known isostatic models: the classical models of Airy/Heiskanen (A/H), Pratt/Hayford (P/H), and Vening Meinesz (VM) and the modern model of Vening Meinesz-Moritz (VMM). The first three models assume a local and regional isostatic compensation, whereas the latter one supposes a global isostatic compensation scheme. A more satisfactory test of isostasy is to determine the Moho interface. The Moho discontinuity (or Moho) is the surface, which marks the boundary between the Earth’s crust and upper mantle. Generally, the Moho interface can be mapped accurately by seismic observations, but limited coverage of seismic data and economic considerations make gravimetric or combined gravimetric-seismic methods a more realistic technique for imaging the Moho interface either regional or global scales. It is the main purpose of this dissertation to investigate an isostatic model with respect to its feasibility to use in recovering the Moho parameters (i.e. Moho depth and Moho density contrast). The study is mostly limited to the VMM model and to the combined approach on regional and global scales. The thesis briefly includes various investigations with the following specific subjects: 1) to investigate the applicability and quality of satellite altimetry data (i.e. marine gravity data) in Moho determination over the oceans using the VMM model, 2) to investigate the need for methodologies using gravimetric data jointly with seismic data (i.e. combined approach) to estimate both the Moho depth and Moho density contrast over regional and global scales, 3) to investigate the spherical terrain correction and its effect on the VMM Moho determination, 4) to investigate the residual isostatic topography (RIT, i.e. difference between actual topography and isostatic topography) and its effect in the VMM Moho estimation, 5) to investigate the application of the lithospheric thermal-pressure correction and its effect on the Moho geometry using the VMM model, 6) Finally, the thesis ends with the application of the classical isostatic models for predicting the geoid height. The main input data used in the VMM model for a Moho recovery is the gravity anomaly/disturbance corrected for the gravitational contributions of mass density variation due in different layers of the Earth’s crust (i.e. stripping gravity corrections) and for the gravity contribution from deeper masses below the crust (i.e. non-isostatic effects). The corrections are computed using the recent seismic crustal model CRUST1.0. Our numerical investigations presented in this thesis demonstrate that 1) the VMM approach is applicable for estimating Moho geometry using a global marine gravity field derived by satellite altimetry and that the possible mean dynamic topography in the marine gravity model does not significantly affect the Moho determination, 2) the combined approach could help in filling-in the gaps in the seismic models and it also provides good fit to other global and regional models more than 90 per cent of the locations, 3) despite the fact that the lateral variation of the crustal depth is rather smooth, the terrain affects the Moho result most significantly in many areas, 4) the application of the RIT correction improves the agreement of our Moho result with some published global Moho models, 5) the application of the lithospheric thermal-pressure correction improves the agreement of VMM Moho model with some other global Moho models, 6) the geoid height cannot be successfully represented by the classical models due to many other gravitational signals from various mass variations within the Earth that affects the geoid.   === QC 20160317